The man who thought he owned water : on the brink with American farms, cities, and food - D'Elgin, Tershia (University Press of Colorado, 2016)
"A story of her small family farm in Colorado with history of water policy in the state and the science and law of water resources in the West. Addressing the deepening need for urban-rural cooperation, dispelling misconceptions and shares essential background knowledge about farms, food and water"--Provided by publisher